2010
DOI: 10.1007/s00134-010-1843-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluids on microvascular perfusion in patients with severe sepsis

Abstract: In this non-randomized trial, fluid administration improved microvascular perfusion in the early but not late phase of sepsis. This effect is independent of global hemodynamic effects and of the type of solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
185
1
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(209 citation statements)
references
References 27 publications
6
185
1
17
Order By: Relevance
“…As a result, the sublingual microcirculation at baseline in our study seems to be less altered when compared with other studies. However, they were similar to microcirculatory parameters in resuscitated septic shock patients [11,12,22]. Considerable microcirculatory interpatient variations are reported in septic shock patients after MAP titration despite fluid resuscitation [12,26], which indicates that the level of MAP should be adapted in consideration of the interindividual effect.…”
Section: ±supporting
confidence: 55%
“…As a result, the sublingual microcirculation at baseline in our study seems to be less altered when compared with other studies. However, they were similar to microcirculatory parameters in resuscitated septic shock patients [11,12,22]. Considerable microcirculatory interpatient variations are reported in septic shock patients after MAP titration despite fluid resuscitation [12,26], which indicates that the level of MAP should be adapted in consideration of the interindividual effect.…”
Section: ±supporting
confidence: 55%
“…Although EGDT is considered to improve microcirculation (23,24) and was associated with lower organ dysfunction-related scores, no benefit in mortality due to multiorgan failure was proven (19).…”
Section: Introductionmentioning
confidence: 99%
“…5 Sidestream darkfield (SDF) imaging is available at the bedside and has been used to directly visualize sublingual capillary beds, thus far predominantly in intensive care unit (ICU) patients with septic shock. 1,[5][6][7][8][9][10] Previous studies demonstrated that observable microcirculatory flow impairment is present in patients with septic shock compared with healthy controls, and persistent impairment after resuscitation to hemodynamic endpoints is associated with increased mortality. 5,6 A prior mouse study showed that microcirculatory flow measured by SDF is markedly decreased in infected mice without hypotension, compared with hypotensive mice with induced hemorrhage.…”
mentioning
confidence: 99%